Analysis of Arabic Teaching at Madrasah Ibtidaiyah Miftahul Ulum Angsokah Timur Madura in the Perspective of Effective Instruction (QAIT Model) Robert E. Slavin - Hamdy, Mohammad Zainal; Ismail, Ali Mahmoud Al Asma'i (Asalibuna, 2024)
Effective instruction is a determinant of success in learning Arabic. With it, learning objectives can be achieved more quickly and are more enjoyable, whereas without them, learning objectives will take longer and tend to be boring. Slavin offers a theory in determining whether learning can be assessed as effective or not, namely by Quality of Instruction, Appropriate Levels of Instruction, Incentive, and Time (QAIT). Therefore, researchers want to know whether learning at Madrasah Miftahul Ulum Angsokah Timur Madura is effective or not by analyzing it with the theory offered by Slavin. This research uses qualitative methods and includes field research. The data collection uses interviews and observations which will then be analyzed using the Miles and Huberman models. The results of this research show that learning at Madrasah Miftahul Ulum Angsokah Timur Madura is effective on one side and less effective on the other side based on Slavin theory, namely effective on the incentive and time side and not on the quality and appropriateness side.